Development of Basic Level Mandarin Reading Learning Media Based on Android - David Darwin; Moh Al-Farizali Aditia; Nabila Halifi (JETL (Journal of Education, Teaching and Learning), 2025)
The development of learning media is a highly appropriate tool to support students' Mandarin reading skills. This study aims to describe the quality, process, and effectiveness of media development in Mandarin reading instruction. The research employs the Research and Development (R&D) method. Data were collected through interviews, observations, and questionnaires, while data analysis was conducted using a descriptive quantitative approach. The results of the study show that the effectiveness of the learning media in the first trial had an average score of 72.5, while in the second trial, it reached an average of 97.5, with an average score of 86 for early reading skills, which falls within the category of a score of 5. From this data analysis, it can be concluded that there is quality, process, and effectiveness in the development of media for Mandarin reading instruction.